Influence of work experience and education towards business performance among entrepreneurs - Othman Nor Hafiza, Md Pazil Afifah Hanim, Attaullah Siti Aishah, Mat Siti Zamanira (Universiti Pendidikan Sultan Idris, 2016)
Influence of work experience and education towards business performance among entrepreneurs by Othman Nor Hafiza, Md Pazil Afifah Hanim, Attaullah Siti Aishah, Mat Siti Zamanira,